Упростите выражения а) (p-2a)(p+2a)-(p-a)(p^2+pa+a^2) б) 3•(2а-5b)^2-12(a-b)^2

0 голосов
187 просмотров

Упростите выражения
а) (p-2a)(p+2a)-(p-a)(p^2+pa+a^2)
б) 3•(2а-5b)^2-12(a-b)^2


Алгебра (182 баллов) | 187 просмотров
Дан 1 ответ
0 голосов

task/29410264                                                                                                                ----------------------                                                                                            Упростите выражения

а) (p-2a)(p+2a)-(p-a)(p²+pa+a² )

б) 3•(2a- 5b)²  - 12(a-b)²

=============

а) (p-2a)(p+2a)-(p-a)(p²+pa+a² )  =p²-(2a)²  -(p³  - a³) = p²- 4a²  - p³ + a³ .

б) 3•(2a- 5b)² - 12(a-b)² =3(4a² -20ab +25b²) - 12(a²-2ab+b²)  = 12a² - 60ab +75b² - 12a² +24ab - 12b² =  63b²  - 36ab .

или

3•(2a- 5b)² - 12(a-b)² =3•( (2a- 5b)²  - 4*(a-b)² )  = 3•( (2a- 5b)²  - (2a-2b)² )  = 3(2a - 5b - 2a +2b)(2a- 5b+2a-2b ) = -9b(4a- 7b ) = 63b²  - 36ab .


(181k баллов)